Hubungan Dukungan Pendamping Sebaya dengan Keterbukaan Status Pada Orang dengan HIV/AIDS - Daramatasia, Wira; Zunaedi, Rosly; Yuliyanik, Yuliyanik (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Disclosure of status among people living with HIV/AIDS (PLWHA) is an important step in improving adherence to antiretroviral therapy (ART) and quality of life. However, social stigma often becomes an obstacle. Peer support can help PLHIV face these challenges by providing information, motivation, and emotional support. This study aims to analyze the relationship between peer support and disclosure of HIV status among PLHIV in the Jombang Care Center Plus community in Jombang Regency. This study uses an observational analytic design with a cross-sectional approach. The sample consisted of 41 active PLHIV respondents, selected through purposive sampling based on inclusion and exclusion criteria. Primary and secondary data were collected and analyzed univariately and bivariately. The instruments used were the Social Provision Scale questionnaire for peer support and the Self Disclosure Scale for disclosure of status. The contingency coefficient correlation test was used to analyze the relationship between variables. The research results show that the majority of PLHIV respondents are adults (97.9%), male (56.4%), have a high school education (48.8%), are married (46.3%), and have the main transmission through sexual relations (51.2%) and MSM (48.8%). Most respondents felt that there was support from peers (63.4%), and 61% were open about their HIV status. There is a significant relationship between peer support and disclosure of status (p = 0.036), where those who received support were more open (73%) compared to those who did not (40%), with a correlation coefficient (r=0.310) indicating a weak to moderate positive relationship. Peer support plays an important role in increasing the disclosure of status among PLHIV. The integration of peer support programs with healthcare services and the enhancement of peer support capacity are recommended to strengthen their impact. Keywords: HIV/AIDS, Peer Support, Disclosure of Status, PLHIV, Stigma  ABSTRAK Keterbukaan status pada orang dengan HIV/AIDS (ODHIV) merupakan langkah penting dalam meningkatkan kepatuhan terapi antiretroviral (ARV) dan kualitas hidup. Namun, stigma sosial sering kali menjadi hambatan. Dukungan pendamping sebaya dapat membantu ODHIV menghadapi tantangan ini dengan memberikan informasi, motivasi, dan dukungan emosional. Penelitian ini bertujuan untuk menganalisis hubungan antara dukungan pendamping sebaya dengan keterbukaan status ODHIV di komunitas Jombang Care Center Plus Kabupaten Jombang. Penelitian ini mengimplementasikan desain penelitian analitik observasional dengan pendekatan potong lintang. Sampel terdiri dari 41 responden ODHIV yang aktif di komunitas Jombang Care Center Plus, dipilih dengan purposive samplingberdasarkan kriteria inklusi dan eksklusi. Data primer dan sekunder dikumpulkan, dianalisis secara univariat dan bivariat. Instrumen yang digunakan adalah kuisioner Social Provision Scale untuk dukungan pendamping sebaya dan Self Disclosure Scale untuk keterbukaan status. Uji korelasi koefisien kontingensi digunakan untuk menganalisis hubungan antar variabel. Hasil penelitian menunjukkan bahwa mayoritas responden ODHIV berusia dewasa (97,9%), laki-laki (56,4%), berpendidikan SMA (48,8%), menikah (46,3%), dengan penularan utama melalui hubungan seksual (51,2%) dan LSL (48,8%). Sebagian besar responden merasakan ada dukungan dari pendamping sebaya (63,4%) dan 61% terbuka tentang status HIV mereka. Terdapat hubungan signifikan antara dukungan pendamping sebaya dengan keterbukaan status ODHIV (p = 0,036), di mana yang mendapat dukungan lebih terbuka (73%) dibanding yang tidak (40%), dengan koefisien korelasi (r=0,310) menunjukkan hubungan positif lemah hingga sedang. Dukungan pendamping sebaya berperan penting dalam meningkatkan keterbukaan status ODHIV. Integrasi program pendampingan dengan layanan kesehatan dan peningkatan kapasitas pendamping sebaya direkomendasikan untuk memperkuat dampaknya. Kata Kunci: HIV/AIDS, Dukungan Pendamping Sebaya, Keterbukaan Status, ODHIV, Stigma